Analysis on the quality formation mechanism and research progress on the preparation process of crystal malt - NIU Limin, ZHANG Yi, LIU Riping, LI Xiaoyan, LI Hui, KANG Wenhuai, CHEN Wenbo (Zhongguo niangzao)
Crystal malt is a kind of special colored malt with caramel flavor, which plays an important role in the increasing flavor, rich color and improving body thickness of craft beer. With the rapid development of global craft beer, the market had put forward higher requirements for the quality and type of crystal malt, and the research on the formation mechanism of crystal malt quality such as flavor and chroma had become more and more important. China as an important part of the global craft beer consumption, there were few studies on the quality of crystal malt, and the theoretical support is relatively weak. The crystallization rate, flavor and color of domestic crystal malt also have great room for improvement. It is of great significance for Chinese crystal malt manufacturers to develop high quality crystal malt products and improve the quality of domestic craft beer based on crystalline malt to carry out comprehensive analysis of the latest research on the formation mechanism of crystal malt flavor and chroma. In this paper, three aspects including the brief introduction, quality formation mechanism and preparation technology of crystal malt were reviewed to provide theoretical reference for further study on crystal malt quality, and a solution for scientific research and production personnel to prepare high-quality crystal malt.